Story Design in Fine Dining Projection Mapping Project “ Si Dulang “ - Yohanes Merci Widiastomo (ULTIMART Jurnal Komunikasi Visual, 2023)
Projection technology is a technology that is familiar to modern society. It has been seen a lot in everyday life, from attending class lectures and watching movies in the theater. Projection technology is also used in creating art, such as projection mapping in various objects. Projection-Mapping is one of the technological achievements that opens complete access for artists to create and tell stories uniquely. Storytelling is something that humans always do over generations. The usage of technology these days is not limited in terms of form. One of the innovative ways to use projection mapping is "le Petit Chef." The combination of fine dining restaurants and the immersive experience when watching animation on a consumer table has positive outcomes for the restaurant industry. Based on the case study of projection mapping named "le Petit Chef", this research will focus on creating a story for projection mapping titled "Si Dulang". This research will also identify the factors the storyteller needs to consider when adopting new technology. Keywords: storytelling; projection mapping; fine dining; animation